Bilateral geminated teeth with talon cusps: A case report - Sener, Sevgi; Unlu, Nimet; Basciftci, Faruk Ayhan; Bozdag, Guldane (European Journal of Dentistry, 2012)
Talon cusps and gemination are rare dental anomalies that can cause significant aesthetic and clinical problems. Bilateral talon cusps on geminated teeth have not been reported so far. The case of gemination with talon cusps on both maxillary central incisors was presented in this report. The main complaints of the patient were tongue irritation and aesthetic problems. The talon cusps were gradually reduced at 2 consecutive sittings and the exposed surface was treated with a fluoride gel. The aesthetical appearance was improved using a composite resin. Fixed orthodontic treatment was initiated for repositioning the left maxillary lateral incisor. A long term, multidisciplinary approach is necessary for the treatment of gemination with talon cusps. (Eur J Dent 2012;6:440-444)
Keywords: Talon cusp; gemination; treatment